SWOT Analysis in Digital Marketing Strategy in Hospitals Lancang Kuning Pekanbaru City in 2023: Analisis Swot Dalam Strategi Pemasaran Digital Di Rumah Sakit Lancang Kuning Kota Pekanbaru Tahun 2023 - Candra, Leon; Athalia Masril, Agnes (Badnur Medisa Group, 2023)
Digital marketing strategy is a business process in promoting a product or brand by utilizing digital technology. In Pekanbaru City, there are many private hospitals of various types that have used digital marketing to promote hospitals. Lancang Kuning Hospital Pekanbaru has carried out digital marketing but is still unable to minimize weaknesses such as the lack of the latest innovations which are the hallmark of Lancang Kuning Hospital's digital marketing in improving Lancang Kuning Hospital's digital marketing. The aim of this research is to determine the digital marketing strategy for Lancang Kuning Hospital in 2023. This type of research is qualitative descriptive research using SWOT analysis. The research was carried out in July- August 2023 at Lancang Kuning Hospital. The informants in this research were 4 people consisting of Operational Manager, Digital Marketing Coordinator, HR Coordinator, and Digital Marketing staff. The results of this research show that Lancang Kuning Hospital's digital marketing already has strengths such as the use of various digital media and advertising features, while the weakness in digital marketing is that new innovations such as providing testimonials through digital media have not yet been implemented. Apart from that, hospitals have marketing opportunities in showing special programs or policies available at the hospital as well as threats in digital marketing, namely the similarity of content and the presence of unfavorable comments on social media. Based on the SWOT analysis of digital marketing, hospitals use an aggressive strategy by using Strength-Opportunity (S-O) factors as a business development strategy. The suggestions in this research are to be able to maintain strength in digital marketing and to increase digital marketing strategy efforts